ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BEBAN PENYEJUKAN PADA BANGUNAN YANG MENGGUNAKAN SISTEM PENGKONDISIAN UDARA ( Studi kasus Gedung Kantor Pusat Politeknik Negeri Manado) - Budhyowati, M. Y. Noorwahyu; Kindangen, Jefrey I.; Tungka, Aristotulus E. (PS S1 Arsitektur. Jurusan Arsitektur, Fakultas Teknik Universitas Sam Ratulangi Manado, 2016)
Indonesia has temperatures 24-32°C, air humidity 60-95% and low wind speeds. Thermally comfortable zone boundary is 24oC<T<26°C, 40% <RH<60%, 0,6<V<1,5m/s. This condition causing the climate of Indonesia becomes uncomfortable. Air conditioning system (AC) is needed to help maintain thermal comfort. The drawback using air conditioning is the wasteful energy use, can reach 60% of total building energy. The amount of electricity used by AC depends on the amount of heat that must be removed to produce cool air. This research aims to analyze the factors that affect the cooling load on the building and get a reference to the way reducing the cooling load, so that the use of electricity more effectively and efficiently. This research conducted by quantitative method with using a case study approach. The focus of research on the orientation of the building as well as the materials and construction techniques used in building walls. The data field collection in object research of Central Office Building of Manado State Polytechnic. Data processing and analysis using descriptive analysis. Data collection are divided on primary data that used in analysis, and secondary data that used as standards/ guidelines for analysis. The results are cooling load on the object of study largely derived from solar radiation heat that into the building, occurred because the building elongated facade orientation tends to block the paths of the sun. Affect the amount of solar radiation intensity received of the building. Most of the walls of buildings using glass and no horizontal exterior shading to protect the vertical rays, thus allowing direct solar radiation through the glass and into the building. The conclusions are that the biggest influenced on the cooling load in the Central Office Building of Manado State Polytechnic caused by the orientation of the building that allows the large amount of solar radiation touch the surface area of the glass. Cooling load reduction could be done in a way; make the horizontal exterior shading but it could change the look of the building facade, or improve the quality of glass within; replacing single glass with double glass or changing the type of glass material, or paste the window film on glass that could be rejected infrared rays. Keywords : cooling load, air conditioning system